Highly branched amine-functionalized p-sulfonatocalix[4]arene decorated with human plasma proteins as a smart, targeted, and stealthy nano-vehicle for the combination chemotherapy of MCF7 cells. (6th July 2018) - Rahimi, Mahdi; Karimian, Ramin; Mostafidi, Elmira; Bahojb Noruzi, Ehsan; Taghizadeh, Sepehr; Shokouhi, Behrooz; Kafil, Hossein Samadi
Abstract : Nanotechnology has recently emerged as a promising field for biomedical applications, especially the targeted delivery of drugs to tumors. Abstract : Nanotechnology has recently emerged as a promising field for biomedical applications, especially the targeted delivery of drugs to tumors. Besides, combination chemotherapy is common in cancer treatment and is rapidly evolving. Therefore, the successfully delivery of chemotherapeutic drugs to targeted cancers is a big challenge. In this study, we endeavour to develop a nano-vehicle, based on highly branched amine-functionalized p -sulfonatocalix[4]arene, to act as a dual-drug carrier for the co-delivery of DOX and MTX to MCF7 breast cancer cells with targeting and synergistic effects. After the synthesis and preparation of the nano-vehicle, structural characterization was also conducted (FTIR, AFM, VSM, SEM, EDX, XRD, DLS, and zeta potential analyses). Drug loading and release studies on the prepared drug-loaded nano-vehicle were conducted to optimize the formulation. The designed platform has targeting and pH-triggered drug release capabilities to improve the therapeutic index of DOX and MTX. Hemolysis assay results proved that the nano-vehicle has high blood compatibility, even for high dosage treatment. The protein–particle interactions of the nano-vehicle in human blood circulation systems were simulated via SDS-PAGE assays and the results indicated that a series of proteins were attached to the surface of the nano-vehicle. This feature gives the nano-vehicle stealth properties in the blood circulation system. The cellular uptake, from flow-cytometry and fluorescence microscopy, validated that the human plasma proteins attached to the nano-vehicle surface gave the nano-vehicle high internalization capabilities into cells due to the presence of some protein receptors on the surfaces of cancer cells, improving the tumor cell targeting properties. MTT assays and DAPI staining were also performed to show the viability and DNA fragmentation of treated cells. All results validated one another and confirmed that our designed nano-vehicle is useful for targeted and combination drug delivery systems with stealth properties.